2018
DOI: 10.1002/jmri.26045
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative susceptibility mapping across two clinical field strengths: Contrast‐to‐noise ratio enhancement at 1.5T

Abstract: 1 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2018;47:1410-1420.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Several observations can be made from our measurements of susceptibility and R2 across a range of GA (under normoxia). Because magnetic susceptibility is independent of field strength, there was no significant difference in susceptibility measures between 1.5T and 3T, showing the 2 linear regression lines nicely overlapped for both mean and SD, which is in accordance with previous results in the brain 33 . In contrast, R2 was significantly higher at 3T than 1.5T, primarily due to increased intravoxel dephasing at a higher field, which is also consistent with results of the brain 34 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Several observations can be made from our measurements of susceptibility and R2 across a range of GA (under normoxia). Because magnetic susceptibility is independent of field strength, there was no significant difference in susceptibility measures between 1.5T and 3T, showing the 2 linear regression lines nicely overlapped for both mean and SD, which is in accordance with previous results in the brain 33 . In contrast, R2 was significantly higher at 3T than 1.5T, primarily due to increased intravoxel dephasing at a higher field, which is also consistent with results of the brain 34 .…”
Section: Discussionsupporting
confidence: 90%
“…Because magnetic susceptibility is independent of field strength, there was no significant difference in susceptibility measures between 1.5T and 3T, showing the 2 linear regression lines nicely overlapped for both mean and SD, which is in accordance with previous results in the brain. 33 In contrast, R * 2 was significantly higher at 3T than 1.5T, primarily due to increased intravoxel dephasing at a higher field, which is also consistent with results of the brain. 34 Also, it was notable that susceptibility and R * 2 showed very different distributions within the placenta as well as different changes with advancing GA. Susceptibility exhibited almost always nearly zero mean, with a symmetrical distribution and increasing SD with advancing GA. For R * 2 , both mean and SD increased with advancing GA; however, given that CV of R * 2 was almost consistent across GA, it can be inferred that spatial heterogeneity of R * 2 within the placenta was maintained, and only magnitude of R * 2 increased as a function of increasing GA.…”
Section: Discussionsupporting
confidence: 87%
“…According to the published methods (14), the QSM reconstruction was achieved through the use of a C++ software developed and validated by Wang and his colleagues (15), and is based on nonlinear morphology-enabled dipole inversion (MEDI), which makes use of the consistency between the susceptibility maps and magnitude images obtained from the Spoiled Gradient Recalled Echo (SPGR) acquisitions. The susceptibility maps are obtained through estimating (nonlinearly) the phase maps, which have to be unwrapped and subsequently undergo dipole inversion.…”
Section: Methodsmentioning
confidence: 99%
“…Brain QSM measurements have good inter-scanner and same-scanner reproducibility for HC and patients, respectively. Ippoliti et al (2018) also evaluated the reproducibility and consistency of QSM across 1.5T and 3.0T field strengths and optimized the contrast-to-noise ratio (CNR) at 1.5T through bandwidth tuning. Feng et al (2018) evaluated the repeatability of QSM on a 3.0T scanner using 8 subjects and found that QSM results were highly reproducible across the four time scans.…”
Section: Introductionmentioning
confidence: 99%